An explicit example concernig the invariant subspace problem for Banach spaces - Śliwa, Wiesław (Rocky Mountain Mathematics Consortium, 2010)
We simplify the negative solution to the invariant subspace problem for Banach spaces. Developing the ideas of Read we give an explicit example of a continuous linear operator on the Banach space of all absolute summable scalar sequences without nontrivial closed invariant subspaces
Keywords: Invariant subspace; Banach space